Questionnaire of Natural Disaster for Mitigational Education - Annisa, Muhsinah; Abrori, Fadhlan Muchlas; Asrani; Prasetio, Teguh; Prastitasari, Herti (LPPM Undiksha, 2024)
Mitigation knowledge is essential, especially for those who live in areas with annual disasters. Therefore, analyzing children's knowledge about mitigation is also necessary because it is the basis for preparing lessons about introducing natural disaster preparedness. This research aims to develop a questionnaire related to natural disaster preparedness based on the cognitive, affective and psychomotor domains. This research is quantitative research using a quantitative descriptive approach. The sampling method used was purposive sampling. The questionnaire development method in this research consists of several stages: itemm preparation, item selection, item sorting, and item validation. The subjects of this research were 5 lecturers, 30 students at the item preparation stage, 2 lecturers and 2 practitioners at the item selection stage, 150 elementary school students at the sorting stage, and 170 elementary school students at the validation stage. The data collection method used is cross-sectional. Then, the questionnaire was created and tested for validity and reliability. The research results show that the developed natural disaster questionnaire for mitigation education meets the requirements for validity and reliability. The research implies that this research can improve disaster mitigation education in schools.